Blastic plasmacytoid dendritic cell neoplasm with genetic mutations in multiple epigenetic modifiers: a case report. Issue 2 (February 2021) - Dang, Xinmei; Zhou, Di; Meng, Lingjun; Bi, Lintao
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare, aggressive hematodermic malignancy derived from plasmacytoid dendritic cell precursors. Despite advances in our understanding of tumor cell surface markers, the pathogenesis of BPDCN remains largely unknown. No standard or optimal treatments are available for BPDCN, and the prognosis is usually poor. We report herein a case of BPDCN that harbored multiple genetic mutations in epigenetic modifiers such as TET2 and ZRSR2 . Genetic studies in patients with BPDCN may provide insights into the underlying pathogenesis, prediction of clinical prognosis, and development of better targeted therapeutics for this rare clinical entity.